Heat treated feeds in turkey feeding - Erdélyi, István; Bársony, Péter; Pálfy, Tamás; Hermán, Istvánné; Pálfy, Tamás (Acta Agraria Debreceniensis, 2007)
The main aim of our study was to determine the effect of expanded and pelleted feeds, as well as the only pelleted feed based on wheat and corn, on the production of turkeys. In May 2006, a fattening experiment on turkeys was started on the starter farm of Habar Ltd in Szarvas, owned by the Gallicoop Corporation. 17 day old male turkeys were involved in the fattening experiment. The experiment lasted 117 days. At that time, theanimals were 134 days old. After the experiment was completed, they were slaughtered. The following parameters were examined: growth, feed conversion ratio, carcass traits. Turkey feed were produced separately at different times. Similarly to the standard method of turkey fattening, 8 phases feeding was carried out. The fattening experiment was adjusted on male turkeys in 4×12×6 grouping (4 treatments: expanded and pelleted, and only pelleted corn and wheat feed; 12 repeats: number of pens/treatments; 6 birds/pen) 6-6 turkeys from 12 pens per each treatments were measured individually from the 17th day (starter) and at the time of each following feeding changes and mortality. The average of the group was calculated. The average daily weight gain, proportion of the given feed per pen, feeding changes and mortality were determined. The average daily feed intake and the feed conversion ratio were calculated.